Al Capsella takes a vacation - Clarke, Judith, 1943- (New York : Holt, 1992)
Sixteen-year-old Al and his best friend Lou vacation without their parents in the wild, partying beach town of Scutchthorpe with unexpected results.
Keywords: Vacations -- Fiction; Friendship -- Fiction; Humorous fiction